2019
DOI: 10.1108/ijot-12-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of sensory processing patterns and their association with demographic factors in healthy adults

Abstract: Purpose Previous research has provided limited evidence on whether and how demographic factors associate with sensory processing patterns (SPP) in adults. This paper aims to examine relationships between SPPs and sociodemographic factors of age, sex, education and ethnicity in healthy adults. Design/methodology/approach A cross-sectional study design was used. A total of 71 adult participants was recruited from the community, using convenience sampling. Each participant completed the Adolescent/Adult Sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This inverse association pattern between sensation seeking and adaptive functioning in individuals diagnosed with ASD compared to those without ASD diagnosis indicates that while sensation seeking behaviors might interfere with adaptive functioning in individuals with ASD, this is not the case for individuals without the condition. Previous research rather suggests that sensation seeking in TD individuals predicts higher functioning, such as higher education and more positive affect (Ben-Avi et al, 2012;Engel-Yeger, & Dunn, 2011;Machingura et al, 2019). Although sensation seeking behaviors might be used by individuals with ASD to regulate under-stimulation and to re-inforce sensory stimuli (Cunningham & Schreibman, 2008;Hebert, 2015), they might also lead to socially unacceptable behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This inverse association pattern between sensation seeking and adaptive functioning in individuals diagnosed with ASD compared to those without ASD diagnosis indicates that while sensation seeking behaviors might interfere with adaptive functioning in individuals with ASD, this is not the case for individuals without the condition. Previous research rather suggests that sensation seeking in TD individuals predicts higher functioning, such as higher education and more positive affect (Ben-Avi et al, 2012;Engel-Yeger, & Dunn, 2011;Machingura et al, 2019). Although sensation seeking behaviors might be used by individuals with ASD to regulate under-stimulation and to re-inforce sensory stimuli (Cunningham & Schreibman, 2008;Hebert, 2015), they might also lead to socially unacceptable behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Sensation avoiding, in particular, is negatively associated with self-care skills such as eating and getting dressed in children with ASD (Jasmin et al, 2009). Interestingly, sensation seeking behaviors, which are associated with positive mood, higher education, and reduced depressive symptoms in TD individuals (Ben-Avi et al, 2012;Engel-Yeger, & Dunn, 2011;Machingura et al, 2019), are in contrast linked to a broad range of behavioral problems, including difficulties in adjusting one's behavior according to social rules (Baker et al, 2008) and academic underachievement in children with ASD diagnosis (Ashburner et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Findings of this study suggest that participants with schizophrenia have a higher neurological threshold than most people and may require more intense stimuli than most people for them to be able to register it. Similarly, previous studies also found that participants with schizophrenia had higher scores than participants without schizophrenia participants Brown et al, 2020;Machingura et al, 2019). This implies that they are less likely to take measures to avoid sensory stimuli that they found to be unpleasant to them.…”
Section: Discussionmentioning
confidence: 66%
“…This study considered whether people with schizophrenia's sensory profiles were atypical when compared with the general population (Machingura et al, 2019). In this study, statistically significant differences in Low Registration and Sensation Avoiding were found between participants who had schizophrenia and healthy participants we had recruited in an earlier study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation